HUMAN BEINGS-IN-SOLIDARITY-WITH- NATURE-AND-GRACE: COSMOTHEANDRIC PERSPECTIVES ON ECOLOGY - Nandhikkara, Jose (Journal of Dharma, 2012)
In our days, even when we live and enjoy the benefits of science and technology, there is a growing awareness that the quality of life is progressively declining and the world peace and even the very existence of life on earth are threatened by lifestyles that lead to the plundering of natural resources for the benefit of the individual, society and humanity in general at the exclusion and exploitation of the rest of the reality, living and non-living. We can no longer remain indifferent to the environmental problems such as, climate change, desertification, deterioration and loss of productivity in vast agricultural areas, the pollution of rivers and aquifers, the loss of biodiversity, the increase of natural catastrophes and the deforestation of equatorial and tropical regions. We cannot afford to forget the simple truth that we live, move and have our being in a network of relations with matter, microbes, plants, animals and other human beings and greater truth that the network of relations is constitutive of our forms of life. Though as human beings we have our unique identity, we form part of the universe with the rest of the world, who are not strangers or enemies but neighbours and partners without whom human life is impossible.